2000
DOI: 10.1002/j.1556-6676.2000.tb02583.x
|View full text |Cite
|
Sign up to set email alerts
|

Report of the ACA Ethics Committee: 1998–1999

Abstract: This report summarizes the activities of the American Counseling Association's (ACA) Ethics Committee for 1998–1999. Summary data of the complaints filed and the inquiries received are presented along with a discussion of the other activities of the ACA Ethics Committee.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Although the ACA ethics committees noted that 276 (52%) of their 1998 inquiries and 300 (48%) of their 1999 inquiries pertained to confidentiality (Brown & Espina, 2000;Shumate & Espina, 1999), inquiries do not translate to complaints against credentialed counselors. In fact, breach of confidentiality constituted only 53 (5%) of the complaints in this study, 42 (5%) in the 1992 study, and 2.6% in the 1987 study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the ACA ethics committees noted that 276 (52%) of their 1998 inquiries and 300 (48%) of their 1999 inquiries pertained to confidentiality (Brown & Espina, 2000;Shumate & Espina, 1999), inquiries do not translate to complaints against credentialed counselors. In fact, breach of confidentiality constituted only 53 (5%) of the complaints in this study, 42 (5%) in the 1992 study, and 2.6% in the 1987 study.…”
Section: Discussionmentioning
confidence: 99%
“…To assist professionals and the public in understanding the extent to which ethical standards are being upheld, the Ethics Committees of the American Counseling Association (ACA) and the American Psychological Association (APA) provide annual reports on the number, nature, and disposition of ethical complaints (see APA, 2000;Brown & Espina, 2000;Shumate & Espina, 1999). However, these associations receive relatively few complaints (e.g., ACA received 14 in 1998 and5 in 1999;APAreceived 42 in 1999), and only a small number are found to be valid and adjudicated through the mechanisms associations have-remediation of the problem or expulsion from the association.…”
mentioning
confidence: 99%
“…Davis et al found between 2% to 23% of the counseling professionals self-reported the likelihood that they would engage in behaviors that exemplify QRPs. In addition to Davis et al's study, ACA's ethics committee reported that approximately 1% of their informal inquiries have been about research and publication (e.g., Brown & Espina, 2000;Kocet & Freeman, 2005;Sanders & Freeman, 2003). Although larger, public cases of research misconduct have not appeared in the counseling profession, the combination of Davis et al's study and ACA's ethics committee reports reveal that, at minimum, QRPs exist within the field of counseling.…”
Section: Research In the Field Of Counselingmentioning
confidence: 92%
“…The field of counseling is not exempt from QRPs and research misconduct, and rates of deviant behavior seem to fit within, or below, Steneck's (2003) suggested range. Over the past 10 years, ACA reported approximately 1% of informal inquiries to the ethics committee related to research and publication practices (e.g., Brown & Espina, 2000;Kocet & Freeman, 2005;Sanders & Freeman, 2003). In addition, Davis, Wester, and King (2008) conducted a study asking members of the Association for Counselor Education and Supervision to respond to eight case vignettes related to research integrity.…”
mentioning
confidence: 99%